PENGARUH SKALA USAHA DAN PENGETAHUAN AKUNTANSI TERHADAP PENGGUNAAN INFORMASI AKUNTANSI PADA UMKM DI KOTA BATAM - Ciki Tasya Tasya (SCIENTIA JOURNAL, 2026)
This study aims to analyze the effect of business scale and accounting knowledge on the use of accounting information among MSMEs in Batam City. The study employs a quantitative method using primary data collected through questionnaires distributed via Google Forms to MSME owners. A total of 100 respondents were selected using a random sampling technique, and the data were analyzed using multiple linear regression. The results indicate that business scale does not have a significant effect on the use of accounting information, while accounting knowledge has a significant effect. These findings suggest that accounting knowledge plays an important role in encouraging MSME owners to utilize accounting information.